Impact blockchain technology on traditional electronic payment system - Ahmed AbdulKarim Talib; Mustafa Hashim Abdulkareem; Saja Nasser Selman; sally AbdulKarim Talib (Institute of Advanced Engineering and Science, 2023)
Every moment there is a new idea and a new project that creates new technologies to make life easier and faster and to invest resources better. In this research, talk about a new technology that is considered a revolution in the age of the Internet, which in turn is the offspring of the new generation of the internet (5G), which is the blockchain technology, which began to be completed and appear to us from 2017, and it is not like other technologies, but in essence depends on changing many of the concepts that we are accustomed to in Communication, exchange and sharing via the Internet, it will change it in the same way as open-source software and in the same way as the Linux system, which, when it appeared, became the main focus for programmers and the development of software technologies, and this is the case with blockchain technology, this technology depends on the user and the customer only. There is no third party or responsible party. The user is responsible here.